Sistematización de cuidados de enfermería en la prevención de infecciones postoperatorias de adultos con artroplastias de cadera - Masache Garces, Cynthia Yessenia (2026)
Hip arthroplasty is the replacement of the hip in the upper part of the femur and the acetabular cavity through surgical treatment. That is why postoperative care in patients with hip arthroplasty is essential to reduce the risk of infection, thereby improving their quality of life. The objective of the research was to systematize the most effective nursing care to reduce the risk of postoperative infections in adult patients undergoing hip arthroplasty through a systematic review of the scientific literature, with the aim of organizing nursing interventions that help patients recover satisfactorily. To this end, the PRISMA methodology was applied to review articles in databases such as Google Scholar, Scielo, Elsevier, Mendeley, and Scopus from 2020 to 2025. The results obtained were reflected in the creation of an updated guide for nursing staff on the care of patients with hip arthroplasty, thus reducing infections and complications that occur after surgery. The challenges involved for nursing staff and caregivers in developing these interventions according to the social context of people undergoing surgical treatment were also analyzed, thanks to the strengthening of the role of nurses in post-surgical patients